ANALISIS KUALITAS PELAYANAN SEKOLAH DI SMK BINAKARYA KARAWANG MENURUT PERSEPSI SISWA - Enjang Sudarman (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2020)
Schools as educational service providers that meet all service criteria. Service quality is very important to know, measured continuously and improved by the school in order to survive in competition. One of the most widely used models in measuring service quality is the SERVQUAL Model by dividing service quality attributes into five dimensions, namely; Tangibles, Reliability, Responsiveness, Empathy, Assurance. This study uses a questionnaire instrument adapted to measure the quality of educational services perceived as a gap between expectations and perceptions of students at Vocational High School Binakarya Karawang. The results of the study obtained a comparison of the perception value of the expectation value (quality index) of 71.21% with an average expectation value of 6.46 and a perception value of 4.60 resulting in a gap of 1.86. These figures indicate that in general the quality of service is still far from what students expect.